A Critical Analysis Of Disciplinary Process Under Labour Law In India Through The Lens Of Principles Of Natural Justice (International Journal of Environmental Sciences, 2025)
The paper presents a doctrinal and contextual analysis of disciplinary jurisprudence in Indian industrial relations, focusing on the evolving application of natural justice principles. It argues that workplace discipline is not merely a managerial tool for ensuring efficiency but a complex legal field that mediates the structural tensions between capital accumulation and labour protection. The study begins by examining how the undefined concept of “misconduct” has been judicially shaped, emphasizing the principles of proportionality and a clear nexus to the employment relationship to prevent arbitrary punishment. A core focus is the domestic enquiry, which the paper analyses as a quasi-judicial process essential for procedural fairness and legitimizing managerial authority within a constitutional framework. By linking disciplinary proceedings to the right to livelihood under Article 21 of the Constitution, Indian courts have elevated these internal processes to a matter of constitutional due process.Through a comparative analysis with labour laws in the UK, China, Germany, and France, the paper highlights the procedural robustness of the Indian model while identifying a need for greater emphasis on substantive compassion. It concludes by advocating for a more dialogic and less adversarial disciplinary framework, proposing the reintroduction of empowered Joint Management Councils (JMCs) modeled on the German Betriebsrat. Such councils would institutionalize a supportive and rehabilitative approach, ensuring termination is a last resort and aligning industrial practice with the constitutional mandate for workers' participation in management.